Analysis of Factors Influencing Consumers in using Loyalty Rewards Programs in Indonesian Convenience Stores using Binary Logistic Regression Method - Putri Syifa Humaira; Annisa Nurwanda Putri; Pratiwi, Pratiwi; Jerry Heikal (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to analyze the factors that influence consumers in using loyalty rewards programs at minimarket retailers in Indonesia. With the backdrop of intense competition in the retail sector, loyalty rewards programs have become one of the main strategies to enhance customer loyalty. This study adopts a quantitative approach using binary logistic regression method to evaluate the influence of the Product, Price, Promotion, and Process variables from the 7P marketing concept on consumer participation. Data were obtained through an online survey of 148 respondents who are consumers of minimarkets with access to the loyalty rewards program. The analysis results show that the Price variable (represented by psychological loyalty), Promotion (represented by product information), and Process (represented by user-friendliness and repeat purchase) have a significant influence on the use of the program. The resulting regression model shows an accuracy of 81.8%, with these variables being the main predictors. The conclusion of this research emphasizes the importance of developing strategies that strengthen the emotional value of the program, optimize promotions, and simplify the program usage process to enhance the effectiveness of the loyalty rewards program. Practical recommendations include exclusive offers for loyal customers, promotions using various digital channels, and integrating the Loyalty Rewards program with digital applications or payment systems to make it easier for consumers to monitor and redeem points, in order to create sustainable added value for both customers and the company.